THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND HYPERTENSION LEVELS IN THE WORKING AREA OF THE PUSKESMAS TANAH TINGGI TANGERANG CITY - Muhamad Yudi Triana; Thoha (Hypertension Prevention and Control Research Center, The Polytechnic of Health of Banten, 2026)
Hypertension is a non-communicable disease (NCD) characterized by blood pressure that exceeds normal limits. It is one of the major risk factors contributing to the global burden of disease. If left untreated, hypertension may lead to serious complications, including stroke, myocardial infarction, kidney failure, heart failure, coronary artery disease, aneurysm, vision loss, and sexual dysfunction. One of the factors associated with hypertension is nutritional status. To determine the relationship between nutritional status and the level of hypertension at Tanah Tinggi Health Center, Tangerang City. This study employed a cross-sectional design with a purposive sampling technique. The sample consisted of 94 respondents. The instruments used included blood pressure measurement to assess hypertension level and body mass index (BMI) measurement to assess nutritional status. The majority of respondents had obese nutritional status, accounting for 50 respondents (53.2%), followed by normal nutritional status in 29 respondents (30.9%) and underweight nutritional status in 15 respondents (16.0%). Most respondents had uncontrolled hypertension, total 54 respondents (57.4%), while 40 respondents (42.6%) had controlled hypertension. The Chi-square test showed a p-value of 0.016, which was less than 0.05. There was a significant relationship between nutritional status and the level of hypertension.